Legal and Linguistic Contradictions in Concept of “Insult” Interpretation - Y. Y. Mageramova (Научный диалог, 2018)
The questions of legal and linguistic interpretations of the concept of “insult” are considered. The relevance is determined by the fact that at the present time appeals of citizens to law enforcement agencies in order to protect their honor, dignity, protect themselves from abuse, attempts to humiliate human dignity are still frequent. The authors draw attention to the following: despite the long-term practice of using the article “Insult” in the course of judicial proceedings and, at first glance, all the obvious signs of insult, in the process of law enforcement there are mutually exclusive interpretations and numerous contradictions, which leads to the need to attract experts-linguists. That is why the article focuses on the consideration of different points of view on the insult in the legal and linguistic spheres, and offers the results of their comparative analysis. The question is raised about the need to take into account a number of factors in the process of linguistic examination of the verbal act of insult, including the peculiarities of regional use of lexical units.